Non-destructive singlepass monitor of longitudinal charge distribution in an ultrarelativistic electron bunch - Logatchov, P.V.; Bak, P.A.; Starostenko, A.A.; Dikansky, N.S.; Tupikov, V.S.; Gubin, K.V.; Mishnev, V.M.; Korabelnikov, M.B.; Fedotov, M.G. (Вопросы атомной науки и техники, 1999)
We present here the first experimental test of a singlepass non-destructive method of monitoring of longitudinal charge distribution in an intensive relativistic electron bunch. This method is based on the scanning of a thin electron beam within the energy range 20-100 keV in the electromagnetic field of an intensive relativistic bunch.